Hospitality and Tourism Entrepreneurship: Administrative Barriers in Imo State, Nigeria. - Nwokorie, Edwin Chigozie; Adiukwu, Kingsley Ikenna (Turizam, 2020)
Impeding factors to the operational efficiency of hospitality and tourism enterprises in Imo State, Southeast Nigeria, were examined in this study. The conceptual model considered if access to funds, government policies and infrastructure determine the efficiency of hospitality and tourism enterprises through the impact on sales volume, cost of operation and productivity. A 21-point questionnaire was administered to 384 respondents of 63 hospitality and tourism enterprises across the state, in which 311 valid instruments were used for analysis. Means and standard deviation were measured in relation to the consequent variables. Hypotheses were tested in Pearson Chi-square to determine significant relationships between the variables and to justify the research model. The result revealed that poor access to funds, inconsistent government policies (like multiple taxation) and poor infrastructure affect sales volume, operating cost and productivity of hospitality and tourism enterprises. The study equally exposed policy weaknesses of the government in providing enabling environment for sustainable hospitality and tourism entrepreneurship, thus leading to poor sectoral development and job loss. Recommendations include the expansion of road networks in the state and prioritization of waste management processes in order to enhance access to hospitality and tourism locations, as well as lessen the overwhelming burden of waste disposal which increases the operating cost of hospitality enterprises.